2021
DOI: 10.47176/mjiri.35.49
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of etomidate, ketamine, sodium thiopental, and midazolam on the mortality of patients with COVID-19 requiring intubation

Abstract: Induction drugs are one of the essential drugs used in intubation and its selection should be made by considering the complications of the drug and patients' clinical condition. However, the researchers have given less attention to the drugs used for the intubation of COVID-19 patients. →What this article adds:This study revealed that the use of etomidate for intubation of COVID-19 patients can be associated with a higher risk of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A retrospective study published in 2021 reported that the use of etomidate was associated with a higher risk of mortality in this population. 13 Another study with COVID-19 patients reported that etomidate possibly contributed to postintubation hemodynamic instability and cardiac arrest. 14 In the present multicenter study, etomidate was associated with lower postintubation MAP, compared to other agents, despite the lower pre-intubation APACHE II score and systolic shock index in the ET group.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study published in 2021 reported that the use of etomidate was associated with a higher risk of mortality in this population. 13 Another study with COVID-19 patients reported that etomidate possibly contributed to postintubation hemodynamic instability and cardiac arrest. 14 In the present multicenter study, etomidate was associated with lower postintubation MAP, compared to other agents, despite the lower pre-intubation APACHE II score and systolic shock index in the ET group.…”
Section: Discussionmentioning
confidence: 99%
“…This practice has been related to a greater number of days of mechanical ventilation and episodes of delirium in ICU patients. 37,38 Several hypotheses associated with the neurotropism of the virus due to episodes of hyperexcitation and agitation have been proposed, 39 which explains the need for deep sedation in patients in the initial phases of ARDS in order to achieve protective ventilation goals. In our study we found a median dose difference between approaches of 5.7 mg/h, which compared with those who received inhaled sedation, who did not require benzodiazepines, suggests a possible decrease in these complications described; however, the reduction we found was not statistically significant in the inhaled sedation group, RR 0.8 (95% CI 0.61-1.15, P ¼ .25).…”
Section: Discussionmentioning
confidence: 99%